Joint photon-number splitting attack on semi-quantum key distribution - Mi, Shang; Dong, Shuang; Hou, Qincheng; Wang, Jindong; Yu, Yafei; Wei, Zhengjun; Zhang, Zhiming (Frontiers in Physics, 2022)
Semi-quantum key distribution is based on the basic principle of quantum mechanics, which allows a classical user and quantum user to use information theory to have a secure shared key. In 2021, our research group proved the first proof-of-principle experimental demonstration of semi-quantum key distribution and verified its feasibility. Due to the limitations of existing science and technology, the experimental system still features a combination of multiphoton signal source and loss in the transmission line. This makes semi-quantum key distribution as susceptible to a photon-number splitting attack as quantum key distribution, leading to limitations of secure transmission distance. It seems that practical single-state semi-quantum key distribution can overcome photon-number splitting attack due to the SIRT bits (also known as the “sifted key”). However, its dual-channel feature still opens up an observation window to Eve. We present two joint photon-number splitting attacks suitable for a single-state semi-quantum key distribution system and show that through the joint photon-number splitting attack, Eve can obtain key information without being detected by Alice or Bob.